Education System in Saudi Arabia - Quamar, Md. Muddassir. author. aut Link
XV, 266 p. 1 illus.
Keywords: This book is a comprehensive study on the education system of Saudi Arabia, placing the reforms and changes it has undergone in the past two decades within the context of the historical evolution of the education system. An education system cannot be seen in isolation of the society; it plays a significant role in shaping the individual, state and the society, that in turn, have a bearing on the education system and its evolution. Therefore, this book locates Saudi education in the backdrop of the changes in the society, how they have facilitated or hindered the education reforms and how the education reforms have impacted the society. The book does not ignore the immediate trigger for the beginning of a comprehensive reforms process but goes beyond it to find much deeper socio-political and economic rationales that paved the way for the reforms. It provides a nuanced understanding of the interplays of various socioeconomic as well as political factors that have shaped the education system in Saudi Arabia. Md. Muddassir Quamar is currently associated with the Manohar Parrikar Institute for Defense Studies and Analyses, New Delhi, India. He has focused his research on the social dynamics in Saudi Arabia within the context of the tensions emerging out of two seemingly non-harmonious trends – Islamization and modernization. He has published several research articles and book chapters on the subject. In addition, he has written extensively on India's evolving relations with the Persian Gulf and Middle Eastern countries. Dr. Quamar was a Visiting Fellow at the King Faisal Center for Research and Islamic Studies, Riyadh in 2014–15.